Treatment strategy for severe blepharoptosis. Issue 1 (January 2020) - Zhou, Xiaobo; Zhu, Ming; Lv, Lin; Jin, Rui; Yang, Jun; Liu, Fei
Abstract: Objective: To establish a treatment protocol for severe blepharoptosis. This protocol helps to achieve improved accuracy and more stable correction outcome. Methods: The levator muscle function was evaluated pre-operation. When the levator function was less than 1 mm, the frontalis suspension technique was performed; when the levator function was more than 1 mm, the techniques of levator resection, combined excision of the tarsus and levator, and tarsus–levator–CFS suspension were performed sequentially until a satisfactory correction result was achieved. Results: A total of 389 patients with severe ptosis (561 eyes) were included; 102 eyes received levator resection, 314 eyes received combined excision of the tarsus and levator, 53 eyes received tarsus–levator–CFS suspension, and 92 eyes received frontalis suspension. In total, a satisfactory correction result was achieved in 466 eyes, while 95 cases still presented with under-correction. The symmetry findings showed that 107 (27%) cases presented good symmetry, 203 (52%) cases presented moderate symmetry, and 79 (21%) showed poor symmetry. Conclusion: This new treatment protocol overcomes the drawbacks of the traditional strategy by standardizing the correction procedure, leading to improved accuracy and more stable correction results.